Reasons for reductions in routine childhood immunisation uptake during the COVID-19 pandemic in low- and middle-income countries: A systematic review - Alexandra M. Cardoso Pinto; Sameed Shariq; Lasith Ranasinghe; Shyam Sundar Budhathoki; Helen Skirrow; Elizabeth Whittaker; James A. Seddon (Public Library of Science (PLoS), 2023)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in a substantial decline in routine immunisation coverage in children globally, especially in low- and middle-income countries (LMICs). This study summarises the reasons for disruptions to routine child immunisations in LMICs. A systematic review (PROSPERO CRD42021286386) was conducted following PRISMA 2020 guidelines. Six databases were searched: MEDLINE, Embase, Global Health, CINAHL, Scopus and MedRxiv, on 11/02/2022. Observational and qualitative studies published from January 2020 onwards were included if exploring reasons for missed immunisations during the COVID-19 pandemic in LMICs. Study appraisal used National Heart, Lung, and Blood Institute and Critical Appraisal Skills Programme tools. Reasons for disruption were defined with descriptive codes; cross-sectional (quantitative) data were summarised as mean percentages of responses weighted by study population, and qualitative data were summarised narratively. A total of thirteen studies were included describing reasons behind disruptions; 7 cross-sectional (quantitative), 5 qualitative and 1 mixed methods. Seventeen reasons for disruptions were identified. In quantitative studies (total respondents = 2,853), the most common reasons identified were fear of COVID-19 and consequential avoidance of health centres (41.2%, SD ±13.3%), followed by transport challenges preventing both families and healthcare professionals from reaching vaccination services (11.1% SD ±16.6%). Most reasons stemmed from reduced healthcare-seeking (83.4%), as opposed to healthcare-delivery issues (15.2%). Qualitative studies showed a more even balance of healthcare-seeking (49.5%) and healthcare-delivery issues (50.5%), with fear of COVID-19 remaining a major identified issue (total respondents = 92). The most common reasons for disruption were parental fear of COVID-19 and avoidance of health services. Health systems must therefore prioritise public health messaging to encourage vaccine uptake and recovery of missed immunisations.